PENERAPAN IOT (INTERNET OF THINGS) PADA SMART HOME UNTUK SISTEM KENDALI MENGGUNAKAN APLIKASI MYSMARTHOME - Hakim, Ardy Rahman; Arnisa Stefanie (Jurnal JE-UNISLA : Electronic Control, Telecomunication, Computer Information and Power System, 2023)
Smart Home system can be interpreted as a house building that is equipped with advanced technology, so that all of these devices and systems can be connected to each other. Only by making a smartphone connection, the user can adjust the opening and closing of the fence using a servo motor, adjust the lighting inside or outside the house, monitor all activities that occur at home, or simply, it can be interpreted that the user manages all the infrastructure of the house using electricity as a generator. it works. In today's era, smart homes have become part of the needs of the middle and upper middle class and millennials who are just entering the world of work. Due to the large demand for smart homes, we designed a smart home system that is connected to an application called MySmartHome system. This smart home is composed of a Wemos as a link between I/O components in the system which are then controlled using the MySmartHome application. In using the MySmartHome application there are two modes in this system, namely control and monitoring mode, in control mode in the form of outputs such as an I2C 16x2 LCD, DC motor, servo and 2 lights which are controlled using this application while monitoring mode starts when the sensor reads a value. , for example the DHT11 sensor reads the temperature and humidity values, an output will be produced in the form of a value in the application that has been made.